Morphometric criteria for evaluating individual territorial units in solving the problem of spatial development of linear objects of terrestrial transport infrastructure - Dmitry V. Kuzmin (International Journal of Advanced Studies, 2025)
Background. The article discusses the issue of evaluating the morphometric properties of a polygon in order to form a rating matrix necessary to solve the problem of finding a path in a discrete space.  This approach to solving the problem of spatial development of linear objects of land transport will be useful in solving practical problems of camera tracing.